Preoperative Patient Education May Decrease Postoperative Opioid Use After Meniscectomy - Steven M. Andelman, M.D.; Daniel Bu, B.S.; Nicholas Debellis, M.D.; Chukwuma Nwachukwu, B.S.; Nebiyu Osman, M.D.; James N. Gladstone, M.D.; Alexis C. Colvin, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation, 2020)
Purpose: To identify the current opioid prescribing and use practices after arthroscopic meniscectomy and to evaluate the role of preoperative patient education in decreasing postoperative opioid consumption. Methods: Patients undergoing arthroscopic meniscectomy were prospectively identified for inclusion. They were placed into 1 of 2 groups: Group 1 received no education regarding opioid use after surgery, whereas group 2 received a standardized overview on postoperative opioid use. Patients were assigned to the groups consecutively: Patients treated at the beginning of the study were assigned to group 1, and patients treated at the end of the study were assigned to group 2. Data from group 1 were used to identify “normal” opioid prescribing and use practices and to guide patients in group 2 regarding normal postoperative opioid use. Patients were surveyed weekly for 4 weeks after surgery to determine the number of opioids taken. Postoperative opioid consumption was analyzed and compared between the 2 groups. Results: A total of 62 patients completed the study (32 in group 1 and 30 in group 2). Patients in group 1 were prescribed an average of 42.0 opioid pills (95% confidence interval [CI], 34.0-51.0 pills) and used an average of 15.84 pills (95% CI, 9.26-22.4 pills) after surgery, whereas patients in group 2 used an average of 4.00 pills (95% CI, 2.12-5.88 pills) after surgery. Patients in group 2 used 11.84 fewer opioid pills (P = .001), a 296% decrease in postoperative opioid consumption. The number of patients who continued to take opioid pills 4 weeks after surgery was 7 patients (21.9%) in group 1 and 1 patient (3.3%) in group 2. Conclusions: Preoperative patient education regarding opioids may decrease postoperative opioid consumption and the duration for which patients take opioid pills after arthroscopic meniscectomy. Level of Evidence: Level II, prospective comparative study.